2023
DOI: 10.57019/jmv.1148015
|View full text |Cite
|
Sign up to set email alerts
|

Development and Transformation in Digital Marketing and Branding with Artificial Intelligence and Digital Technologies Dynamics in the Metaverse Universe

Abstract: The Metaverse will have a variety of effects on marketing. Businesses need to maintain their identities in the Metaverse realm. Generation Z and Generation alpha will have an easier time adjusting to virtual realms. The augmented reality environment allows buyers to interact with products without leaving the comfort of their own homes. Realization of in-store experiences is possible in the universe of the Metaverse. In addition, there will be an increase in the number of options for branding in the Metaverse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(29 citation statements)
references
References 38 publications
0
27
0
2
Order By: Relevance
“…The overarching potential of the metaverse showcased in numerous past and currently related projects have brought considerable investments to the sector from businesses across differing disciplines (Nalbant and Uyanik, 2021). This implies that the investors in the metaverse sector are fairly optimistic about metaverse’s growth potential as well as confident that they could harvest them in a profitable manner.…”
Section: Discussionmentioning
confidence: 99%
“…The overarching potential of the metaverse showcased in numerous past and currently related projects have brought considerable investments to the sector from businesses across differing disciplines (Nalbant and Uyanik, 2021). This implies that the investors in the metaverse sector are fairly optimistic about metaverse’s growth potential as well as confident that they could harvest them in a profitable manner.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, Nalbant and Aydin (2023) observed that the successful advancement of the Metaverse and digital transformation is crucial for the progress of both nations and individual businesses. Virtual worlds possess the potential to revolutionize communication, product advertising, and customer service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intelligent Landscape Design Methods: In the field of landscape design, AI technology can help designers analyze the geography, climate, soil, and other characteristics of a site to optimize vegetation configurations and material choices for more sustainable and environmentally friendly designs [27][28][29][30][31][32] . At the same time, intelligent algorithms can also assist in spatial planning to enhance the utilization efficiency of the site and the flow of people.…”
Section: Related Workmentioning
confidence: 99%